Right ventricular outflow tract dimensions in arrhythmogenic right ventricular cardiomyopathy/dysplasia—a multicentre study comparing echocardiography and cardiovascular magnetic resonance. (26th May 2017) - Gotschy, Alexander; Saguner, Ardan M; Niemann, Markus; Hamada, Sandra; Akdis, Deniz; Yoon, Ji-Na; Parmon, Elena V; Delgado, Victoria; Bax, Jeroen J; Kozerke, Sebastian; Brunckhorst, Corinna; Duru, Firat; et al.
Abstract: Aims: Right ventricular outflow tract (RVOT) dilation is one of the echocardiographic criteria in the 2010 revised Task Force Criteria (TFC) of arrhythmogenic right ventricular cardiomyopathy/dysplasia (ARVC/D). However, studies comparing cardiac magnetic resonance (CMR) and transthoracic echocardiography (TTE) suggest a lower diagnostic accuracy of TTE due to its operator dependence and limited reproducibility. The goal of this study was to compare the 2010 TFC measures of RVOT dilation with three alternative measures for improving the echocardiographic assessment of RVOT in patients with ARVC/D. Methods and results: In this multicentre study, CMR and TTE were performed in 38 patients with a definite, borderline, or possible ARVC/D diagnosis and in 10 healthy controls. Besides the echocardiographic RVOT measurements listed by the 2010 TFC, we assessed three additional end-diastolic RVOT diameters. These included the RVOT diameter defined by the parasternal long axis M-mode of the aortic sinus portion (RVOT3), that defined by the parasternal long axis M-mode of the left ventricle (RVOT4), and that obtained by the parasternal short axis view of the distal RVOT proximal to the pulmonary valve (RVOT5). RVOT4 provided the best correlation between CMR and TTE ( r  = 0.92, [95% confidence interval (CI): 0.84–0.96; P  < 0.0001]) and enhanced diagnostic accuracy for diagnosing ARVC/D (area under the curve 0.92 [95% CI, 0.78–0.98]). Conclusion: Among all RVOT diameters examined, that defined by the parasternal long axis M-mode of the left ventricle (RVOT4) provides the best agreement between CMR and TTE and exhibits the best diagnostic accuracy for ARVC/D. This novel RVOT4 measurement carries the potential for improving the echocardiographic diagnosis of ARVC/D.